2011
DOI: 10.1016/j.heares.2010.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Conditional deletion of Atoh1 using Pax2-Cre results in viable mice without differentiated cochlear hair cells that have lost most of the organ of Corti

Abstract: Atonal homolog1 (Atoh1, formerly Math1) is a crucial bHLH transcription factor for inner ear hair cell differentiation. Its absence in embryos results in complete absence of mature hair cells at birth and its misexpression can generate extra hair cells. Thus Atoh1 may be both necessary and sufficient for hair cell differentiation in the ear. Atoh1 null mice die at birth and have some undifferentiated cells in sensory epithelia carrying Atoh1 markers. The fate of these undifferentiated cells in neonates is unkn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
194
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 109 publications
(211 citation statements)
references
References 71 publications
15
194
1
1
Order By: Relevance
“…Similarly, three rows of OHCs and one row of IHCs together with supporting cells were also observed in the cochlear section preparation (Fig 2B). In Atoh1 -CKO mice, no Myo7a-positive cells were observed in the entire length of the cochlea and the organ of Corti was replaced by a flat epithelium consisting of BMP4 positive Claudius cells [15,35]. An example of the lack of Myo7a-positive cells from the apical turn is shown in Fig 2C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, three rows of OHCs and one row of IHCs together with supporting cells were also observed in the cochlear section preparation (Fig 2B). In Atoh1 -CKO mice, no Myo7a-positive cells were observed in the entire length of the cochlea and the organ of Corti was replaced by a flat epithelium consisting of BMP4 positive Claudius cells [15,35]. An example of the lack of Myo7a-positive cells from the apical turn is shown in Fig 2C.…”
Section: Resultsmentioning
confidence: 99%
“…This K + recycling loop is assumed to be important for maintaining the EP and homeostasis of the ion composition in the endolymph [4]. In the Atoh1 -CKO mice, this pathway is no longer present since the entire organ of Corti degenerates and the basilar membrane only contains one to two layers of epithelial cells [35]. One would expect that the EP magnitude would drop if this recycling loop is no longer present.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed, however, that cells that look histologically similar to SCs are present at P0 (Bermingham et al 1999), and the structure of the tissue is consistent with wild-type patterning at E16.5, E18.5, and P1 Dabdoub et al 2008;Pan et al 2010). It has been demonstrated that specification of the sensory epithelium is independent of Atoh1 (Chen et al 2002;Dabdoub et al 2008); this would mean that, during early development of the OC, SC markers such as Sox2, Prox1, and Jagged1 would be detected in Atoh1-null animals, as these factors are required for early patterning.…”
Section: Atoh1 and Auditory Hair Cellsmentioning
confidence: 90%
“…The cochlea of a homozygous Atoh1 mutant mouse lacks differentiated HCs. Histological analysis and electron micrographs of cochlear tissue throughout development and at P0 show that, within the zone usually assigned to the OC, HCs are absent (Bermingham et al 1999;Pan et al 2010). Further analysis using immunohistochemistry and ISH to identify individual cell types at P0 showed that not only are there no cells expressing HC markers such as myosin 6 and calretinin, but that there are also no cells expressing markers of the various organ of Corti supporting cells (SCs), including inner pillar cells (probed for Jagged1, Fgfr3, TC2, and p75 ntr ), Deiters' cells (probed for Jagged1, glial fibrillary acidic protein, TC2, and Fgfr3) and phalangeal cells (probed for Jagged1 and glial fibrillary acidic protein) (Woods et al 2004).…”
Section: Atoh1 and Auditory Hair Cellsmentioning
confidence: 99%
“…Other loss-of-function studies showed that Atoh1 drives HC differentiation (Bermingham et al, 1999;Fritzsch et al, 2005;Pan et al, 2011), and overexpression of Atoh1 transformed non-sensory cells into HCs (Kelly et al, 2012;Zheng and Gao, 2000). Atoh1 differentiates HCs in the ear, and the level and duration of Atoh1 expression regulate different types of HCs and their viability Sheykholeslami et al, 2013).…”
Section: Introductionmentioning
confidence: 99%